KONSENTRASI LOGAM BERAT DI PERAIRAN, SEDIMEN DAN BIOTA DENGAN FAKTOR BIOKONSENTRASINYA DI PERAIRAN BATU BELUBANG, KAB. BANGKA TENGAH - Wahyuni, Hasti; Sasongko, Setia Budi; Sasongko, Dwi P (Universitas Diponegoro, 2013)
Abstract Â The reduction of land that used for land-based mining caused the shift of mining from land-based mining to off-shore mining, that used to namedFloating Inkonvensional Mining. This type of mining caused waters quality degradation.This research aimed to analyze Pb, Cd, and Zn content in water, sediment, and biota so that the value of the bio-accumulation factor can beanalyzed.The locations determination was conducted by using purposive random sampling method and the implementation was using GPS Garmin 60 in June 2013. The sea water sampling was using the water sampler, the sediment sampling was using paralon pipe, the plankton sampling was using the plankton-net, the shellfishes sample was collected from the fishermen, and the chavies and squids sample was got from Baganin the waters of Pulau Panjang.The analysis of the metal in water and sediment was refer to the prosedur standard method (APHA, 2005), while the analysis of the heavy metal in the planktons and the tissue of the biota was refer to SNI 2354.5:2011. The content of metal was compared with the quality standard that have been determined.The Cd and Zn content in water was under the sea water quality standard for sea biota. The Pb in the waters have been exceeded the quality standard that have been determined in Kepmen LH no. 51 Tahun 2004.The Pb, Cd, and Zn content in sediment wasÂ lower and far away from the quality sandard that have been determined by Norwegia and Irlandia. The heavy metal content in Anadara granosa, Stolephorus, sp, and Loligo chinensis, gray which were got chaught in the waters of Batu Belubang was lower thanthe national quality standard (SNI 2731.1:2010). The value of bio-concentration factor (BCFs-w) showed that the highest ability of sediment to accumulate Pb was existed in station number 2, i.e. 10,037 l/kg. The value of bio-concentration factor (BCFo-s) showed the plankton ability to accumulate Pb in sediment (1,26) was higher than its ability to accumulate Zn in sediment (1,22), while its ability to accumulate metal in water (BCFo-w) was as high as 8,275 in station number 2. The value of bio-concentration factor (BCFo-s) showed that the shellfish, chavies, and squid ability in accumulating metal in sediment was as high as 0,713; 0,564 and 0,703. The value of bio-accumulation of shellfish in sediment was higher because sediment was the habitat of shellfish.Floating Inkonvensional Mininghave contribution in spreading heavy metal, that was contained in the soil, to the waters. This condition needs supervision to control TI Apung growth in this location so that does not pollute the waters. Kata kunci : Lead(Pb), Cadmium (Cd), Zink (Zn), Water, Sediment,Plankton, Shellfish, Chavies,Squid, Batu Belubang, Floating Inkonvensional Mining, Bio-concentration Factor (BCF). Â